On the reduction of disinflation costs: fixed exchange rates or central bank independence? - DE HAAN, J.; KNOT, K.; STURM, J.E. (PSL Quarterly Review, 2013)
Cost management has become a major strategic issue in world banking as revenues become harder to earn and loss provisions erode a large proportion of banks' net interest income. This article summarises a recent, extensive study on cost management in global banking that was conducted by Salomon Brothers and published in October 1993. The study covered 50 major banks in 11 countries. JEL: E52, E58